Optimal Use of Plant Growth Regulators for Improved Growth, Yield, and Economic Returns of Winter Tomato (Solanum lycopersicum) in arid regions: OPTIMIZATION OF PLANT GROWTH REGULATORS USE IN TOMATO - Choudhary, Santosh; Suman Poonia; S. K. Moond; P.R. Raiger; Moola Ram; Ronak Kuri (Annals of Arid Zone, 2024)
A field experiment was conducted to optimize the application of plant growth regulators in tomato cultivation during rabi, 2021-22. The objective was to assess their effects on growth, yield attributes, fruit yield, and economics. The experiment included 10 treatments with three plant growth regulators (GA3, 4-CPA, and NAA), each applied at three levels (25, 50, and 75 µg mL-1), along with a control (water). The experimental design was a randomized block with three replications. Results indicated that GA3 and NAA significantly enhanced plant height, the number of branches, fruit yield, and economic returns. Conversely, 4-CPA adversely affected yield and consequently economic returns. Optimal dosages for GA3 and NAA were identified at 53.5 µg mL-1 and 63.1 µg mL-1, respectively, using second-order polynomial regression (y=ax2+bx+c). This resulted in tomato yields of 29.55 and 29.69 t ha-1, respectively. NAA treatments stood out, providing the highest net returns (Rs. 4,80,447 ha-1) and a favourable B:C ratio of 4.26:1, making it a promising choice for tomato cultivation